Risk of food poisoning involving enterotoxigenic staphylococci carriers - Herrero, Francisco; Hirooka, Elisa Yoko (Semina: Ciências Agrárias, 1993)
<!--[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Healthy carriages constitute major reservoir of enterotoxigenic staphylococci. The intoxication occurs after ingestion of manipulated foods, maintained at inadequate preservation. This review discusses about the epidemiology at the interaction level between hospital professionals and food handlers, transferences of microorganisms and the possible development of enteroxigenic strains with high antibiotic resistence.